Wall roughness influence on the efficiency characteristics of centrifugal pump - Lipej, Andrej (Strojniški vestnik, 2017)
Many different machines are developed in industry and in terms of energy conversion, their efficiency is one of the most important parameters. A lot of theoretical, experimental and numerical analyses are done in the development process in order to obtain required characteristics. Computational fluid dynamics (CFD) analyses are a very important part of the development process. To obtain accurate results it is important to pay attention to geometry definition, usage appropriate numerical model, quality of the computational grid, realistic boundary conditions and all of the other parameters regarding fluid and solid material properties. A very important issue is usually the correct selection of the turbulence model. In most CFD analyses, only smooth surface is taken into account without considering any wall roughness. Besides the usage of different physical and mathematical models and all required parameters, the wetted surface roughness can also be one of the important origins of the numerical results inaccuracy. In the paper, the analysis of the influence of different parameters such as the sandgrain equivalent parameter is presented. The influence of y+ on the accuracy of the flow analysis with different absolute roughness of the surfaces is also analyzed. For basic relations, the flow in simple geometries like flow over flat plate and flow in circular pipe has been analyzed. The conclusions of the preliminary research work are used in the case of efficiency prediction of centrifugal pump with rough walls. The final numerical results are compared with the experimental ones and show better agreement in comparison with the flow over smooth walls.
Keywords: črpalke; hrapavost; numerična dinamika tekočin; turbulence